2005
DOI: 10.1029/2004jb003153
|View full text |Cite
|
Sign up to set email alerts
|

Sublithospheric small‐scale convection and its implications for the residual topography at old ocean basins and the plate model

Abstract: [1] The seafloor topography and heat flux differ significantly from the predictions of the half-space cooling (HSC) model at old ocean basins. Understanding the deviations has important implications for thermal evolution of oceanic lithosphere and large-scale mantle dynamics. A widely used model that explains significant fraction of the deviations is the plate model, but the dynamical feasibility of the plate model has never been demonstrated. In this study, we investigated the effects of sublithospheric small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 73 publications
6
88
0
1
Order By: Relevance
“…Such cooling is observed in earlier studies [24,39,40], although adding internal heating to the model might reduce or even completely compensate for this cooling [40]. This cooling increases the local viscosity, which delays the formation of TBI, but the amount of erosion by TBI is not significantly affected, as discussed above on the basis of two cases with different rates of accumulation of cold downwellings in the upper mantle due to different ∆η values.…”
Section: Wu Valuesmentioning
confidence: 49%
See 1 more Smart Citation
“…Such cooling is observed in earlier studies [24,39,40], although adding internal heating to the model might reduce or even completely compensate for this cooling [40]. This cooling increases the local viscosity, which delays the formation of TBI, but the amount of erosion by TBI is not significantly affected, as discussed above on the basis of two cases with different rates of accumulation of cold downwellings in the upper mantle due to different ∆η values.…”
Section: Wu Valuesmentioning
confidence: 49%
“…This may lead to increased heat flux and decreased topographic subsidence (i.e., topographic flattening) at relatively old seafloor, compared to the purely conductive cooling model predictions [18]. Although O'Connell and Hager [39] and Davies [44] suggested that by enhancing the cooling of the mantle the TBI may lead to deepened seafloor topography, Huang and Zhong [40] recently demonstrated using mantle convection models with a reasonable internal heating rate that the TBI produces topographic flattening at the surface, supporting the original suggestion by Parsons and McKenzie [18].…”
Section: Wu Valuesmentioning
confidence: 99%
“…Similar values have been extensively used in earlier studies on SSC (e.g. [11][12][13][14]), allowing qualitative comparisons between these and our models. We emphasise, however, that these activation energy and pre-exponential factor values are too low to be consistent with currently available laboratory experiments on diffusion creep (e.g.…”
Section: General Features Of Small-scale Convectionmentioning
confidence: 69%
“…To avoid these undesired effects we use a free-slip condition in regions near both corners, which leads to the generation of a smoother corner flow. For similar reasons, we further introduce two small weak zones near the upper corners (see Figure 1a), as commonly done in similar studies [12]. The viscosity in these regions is divided by 10, 100 or 1000 depending on the model.…”
Section: Model Setup and Boundary Conditionsmentioning
confidence: 99%
“…van Hunen et al, 2005). The plate model does not explicitly describe the physics of this transition, but provides a good fit to the bathymetry and heatflow data (Huang and Zhong, 2005). Gravitational instabilities of the thickening lithosphere are not explicitly included in our model, but the average reduction in lithospheric thickening of any detaching or delaminating lithosphere is accounted for by the plate model.…”
Section: Methodsmentioning
confidence: 99%